2012
DOI: 10.1016/j.jtice.2011.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide removal by a mixed culture of bacteria and white-rot fungi

Abstract: Combining activated sludge cultures with microbes harboring specific degradation pathways could constitute a relevant process for the removal of toxic and recalcitrant organic substances from wastewater. Enhanced removal of three widely used recalcitrant pesticides from their liquid mixture was demonstrated by implementing a non-acclimated mixed culture of bacteria and white rot fungus. During an incubation period of 14 days, the mixed fungusbacteria culture achieved 47, 98, and 62% removal of aldicarb, atrazi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 113 publications
(46 citation statements)
references
References 14 publications
2
41
0
3
Order By: Relevance
“…This observation points to a synergistic effect achievable by combining a mixed culture of bacteria and white-rot fungus. Our observation is in line with another study where enhanced removal of three pesticides from their mixture was demonstrated by a mixed culture of bacteria and white-rot fungus as compared to bacteria or white-rot fungus -only cultures (Hai et al, 2012a …”
Section: [Figure 2]supporting
confidence: 92%
“…This observation points to a synergistic effect achievable by combining a mixed culture of bacteria and white-rot fungus. Our observation is in line with another study where enhanced removal of three pesticides from their mixture was demonstrated by a mixed culture of bacteria and white-rot fungus as compared to bacteria or white-rot fungus -only cultures (Hai et al, 2012a …”
Section: [Figure 2]supporting
confidence: 92%
“…Probably for that reason (it is a common herbicide for sunflowers), only a few researches can be found in the articles of northern developed countries and in the literature. Also it can be seen in the literature that a few studies have explored the combination of fungi and bacteria to remove pesticide from the aqueous phase [12]. For that reason, our study has an importance to complete the information in the literature.…”
Section: Journal Of Chemistrymentioning
confidence: 98%
“…It was reported that the mineralization of some pesticides was mainly due to fungal activity. However, pesticides were not degraded when fungi or bacteria were separately inhibited [12].…”
Section: Witnessmentioning
confidence: 99%
See 1 more Smart Citation
“…Mixed cultures of bacteria and WRF have been found to remove TrOCs from wastewater via biodegradation and biosorption [158,159]. There is also evidence that WRF can eliminate TrOCs from biosolids.…”
Section: Bioaugmentationmentioning
confidence: 99%